If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + 7 + -3x = 4x + -10 Reorder the terms: 7 + 13x + -3x = 4x + -10 Combine like terms: 13x + -3x = 10x 7 + 10x = 4x + -10 Reorder the terms: 7 + 10x = -10 + 4x Solving 7 + 10x = -10 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 7 + 10x + -4x = -10 + 4x + -4x Combine like terms: 10x + -4x = 6x 7 + 6x = -10 + 4x + -4x Combine like terms: 4x + -4x = 0 7 + 6x = -10 + 0 7 + 6x = -10 Add '-7' to each side of the equation. 7 + -7 + 6x = -10 + -7 Combine like terms: 7 + -7 = 0 0 + 6x = -10 + -7 6x = -10 + -7 Combine like terms: -10 + -7 = -17 6x = -17 Divide each side by '6'. x = -2.833333333 Simplifying x = -2.833333333
| 95x+0=70x+70*450 | | m^2+5m+6= | | -3+y+6=5y+19 | | 7x+16=8x+7 | | c=qn+q | | 8x-(6x+7)=3 | | x+(x+3)+(x+7)=40 | | .3(x)+150(.5)=.5 | | 0.1*x+0.6*40=0.4 | | .1(x)+.6(40)=.4 | | 24x-5-18x+2=18-7-12x+15 | | 89x+8(82)=87(x+8) | | 89(X)+8(82)=87(x+8) | | x+3/4+9=0 | | x+(-11/2)+9=0 | | 5x^2=60-20x | | 2w^2-128=0 | | 3x-4=2(3x+2)-3x | | 3x^2+84=33x | | -8/3+y+9=0 | | 6x+7-9x=16-14x+11-9 | | 200+1x=160+4x | | log(x-9)=1-logx | | log(x-0)=1-logx | | (2y+7)(5+y)=0 | | 64-9u^2= | | -3x-10x=-52 | | 3(w+2)+w=4(w-1)+9 | | 12x-9=15x-3 | | -3(u+2)=2(u+6)+7 | | -0.5(x+8.5)=-0.3x-10.3 | | -3(x+5)+5x=2x-6 |